The development of communication technologies and their impact on the existing theories in the fieldof media gate guard theory as a model - Hussein, Hussein Naser (Thi Qar Arts Journal, 2023)
The research aims to explore whether technological developments over the past two decades have impacted the gatekeeper theory, as we were noting that technological developments in recent years have made it easy for anyone to publish any content and information without need for a gatekeeper in traditional media. So we are seeing there is an increase of criticism directed at the theory, which is one of the basic theories in communication science, as most of those who criticize the theory claim to be not appropriate for the changes by technological development in the field of mass media, And to identify the most important variables and factors created by the conditions of technological changes, which characterized the features of the modern communication environment, and to know whether it limited the ability of the theory to interpret the factors that control the conditions of the flow of media contents and communication messages to the public, in this point the problem of research it is becoming clear, which presented it by a set of questions to get accurate scientific answers to it.The researcher began the project by historical review of the origins of the scientific theory by (Kurt Lewin), and reviewing the context in which the theory and the most important stages of development and studies conducted by many researchers who study of theory and worked on the development of concept, Seeking the most important factors affecting the work of gatekeeper.The researcher reviewed the most important technical and technological changes in the field of communication and the consequent effects that changed the form and concept of communication process, as technological change does not happen and does not continue for itself, but must lead to a many changes in the related fields, especially in the field of mass media changes, And therefore must lead to change the concepts that govern the process fully.Therefore, the researcher reviewed the most important developments and the scientific opinions and views on the effects of the development of communication technologies, in which the public turns into an active part of communication process, not only a receiver and consumer of the information, but a part has ability to participation, interaction and transformation from receiver to sender as gatekeeper according to critics of the theory.To measure the impact of technological developments on gatekeeping theory, the researcher prepared a questionnaire that included a set of questions includes all important topics of research paper.The important results of research are:• The results of the study indicated that more than 96% of the research sample believes that communicator as a gatekeeper still care of many considerations before publishing the news. The most important considerations that come first is media policy, then the public, fear of political parties and armed movements, and advertisers.• The results of the study indicated that most of communicator who participated in the study (more than 65%) blocked some news and don't send it to publish. The study also indicated that about 65% ​​of sample is working to avoid covering events that could cause them troubles with political parties.• The results of study showed that the majority of the surveyed communicators believe that contemporary technology has had a clear impact on gatekeeping theory. It cannot be ignored, but this effect does not end the gatekeeping theory.The theory of the gatekeeping is related with the newsrooms and is controlled by many motives. The new media did not end the traditional media, but the international and regional news and media institutions are still active, present as an important source of news for the public. It is not true to say that the new media conceal the old media.The results of the research show that more than 66.67% of the sample believes that the traditional model of gatekeeping theory needs to be rewriting it in the light of modern developments of communication technologies to accommodate with the changes in the field of communication. While more than 28% of the sample of the study believes the gatekeeping theory is still active in the field of media and was not affected by the technological developments in the field of media.To say that the theory needs to be reformed under the current developments of communication technologies that it is still active and effective in the field of mass media. The technological developments has not led to the end of the theory, but its just need to review in the light of recent technological developments the previous results clearly indicate that the theory is effective for communicators in the field of news.While only 5% of sample believes that the theory is no longer to be active in the field. but those who see this is a very small percentage, and this opinion is contrary to all indicators and results of study The gatekeeper's theory that indicates it is very active and presents in the work of the communicator as a gatekeeper. We noted that the communicator cares of many considerations before publishing the news, such as the channel's news policy, professional considerations, fear of political parties and armed forces.